PREVALENCE AND RISK FACTORS OF VARICOSE VEINS OF LOWER LIMBS AMONG THE EMPLOYEES OF CLEANING OF A PRIVATE INSTITUTION, CITY OF CASCAVEL – PR (Fiep Bulletin - online, 2016)
Introduction: Varicose veins are characterized as tortuosity, stretching and increased diameter of the veins of lower limbs. The venous disease is an important public health problem. Objective: To determine the prevalence and risk factors of varicose veins in the cleaning employees of a private institution, in the city of Cascavel-Pr. Methods: 60 women between 18 and 60 years were interviewed; they are employees of cleaning in a private institution of higher education, Assis Gurgacz University - FAG in the city of Cascavel-Pr. A questionnaire was written by the researchers and applied in June 2014, during the time the employees were available. For statistical analysis, data were tabulated in Microsoft Office Excel 2007 and analyzed using SPSS 15.0 software. Results: 90% of women have varicose veins (from these, 66.7% have telangiectasia and 23.3% higher caliber varices) and 10% guaranteed not having varicose veins. It was found that increasing age increases the incidence of varicose veins, brown and white race have greater involvement, but risk factors such as BMI, sedentary lifestyle, genetics and medication do not influence directly the presence of varicose veins in this sample. Conclusion: The study revealed a high prevalence of varicose veins in cleaning employees of the institution and that there is a need to develop health programs for prevention, diagnosis and treatment of this disease.
Keywords: prevalence; risk factors; varicose veins.